Quina lenga per revitalizar l’occitan ? - Cristian Lagarda (Lengas)
The article analyses the results of a written survey of 20 teachers of French higher education in Occitan-Langue d’oc. After an incursion into the teacher’s personal linguistic biography and professional language, it focuses on the evaluation of the students from the point of view of language varieties, their competences, and it ends, in the prospective, on their motivations and their possibilities of transmitting the language –for those who will teach. The self-reflexive and polyphonic exercise highlights the issues and a certain consensus on the part of the actors.